A decade of restoring a temperate woodland: Lessons learned and future directions. (30th December 2021) - Harrison, Peter A.; Davidson, Neil J.; Bailey, Tanya G.; Jones, Menna; Gilfedder, Louise; Bridle, Kerry; Bowman, David M. J. S.; Baker, Thomas P.; Richardson, Benjamin J.; Wallis, Louise; Potts, Brad M.
Summary: We synthesise the findings from 10 years of ecological restoration in the Midlands of Tasmania, Australia, captured in the series of 14 papers in this special issue of Ecological Management and Restoration. The papers illustrate how expertise from disciplines as diverse as law, economics, social sciences, the arts, education, zoology, botany, genetics, climate modelling, agriculture, spatial sciences and fire ecology are necessary to address the complex social, ecological and financial questions that underpin restoration ecology. We highlight the complexity of the task, the multi‐disciplinary and collaborative approach needed, the importance of science to inform restoration practice and the problem of achieving functional connectivity. We also outline steps that need to be taken in the next 10 years. Together, the outcomes and recommendations from these studies provide a template for restoration in similar highly cleared and degraded agricultural landscapes affected by climate change in Australia and internationally.